Eccrine Angiomatous Hamartoma: A Review of Ten Cases - Shin, Jaeyoung (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2013)
BACKGROUND: Eccrine angiomatous hamartoma (EAH) is a rare benign nodular lesion characterized by the proliferation of eccrine and vascular structures, generally capillaries, in the middle and deep dermis. It may be congenital or appear later in childhood, but rarely arises in adulthood. OBJECTIVE: To investigate the clinicopathologic features of EAH in Korean patients. METHODS: Ten cases of EAH diagnosed at Ajou University Hospital and Gangnam Severance Hospital in Korea from 2007 to 2010 were retrospectively reviewed. RESULTS: The age range of patients was between 5 and 66 years with an equal number of male and female patients. Apart from two congenital cases, the onset was late, ranging from 6 months to 65 years of age. All lesions were solitary and located on the distal extremities. Nine cases appeared as a yellow-brown nodule or plaque resembling a callus. Neither hyperhidrosis nor hypertrichosis was documented. Apart from the typical histological findings of EAH, prominent mucin deposition, fat component and nerve infiltration were observed. CONCLUSION: This is one of the largest single case series of EAH in the literature. Clinically, resemblance to callosities and the frequent occurrence in the adulthood were the unique features in our series.